2004
DOI: 10.1083/jcb.200403174
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma chondroitin sulfate proteoglycan enhances FAK and ERK activation by distinct mechanisms

Abstract: Melanoma chondroitin sulfate proteoglycan (MCSP) is an early cell surface melanoma progression marker implicated in stimulating tumor cell proliferation, migration, and invasion. Focal adhesion kinase (FAK) plays a pivotal role in integrating growth factor and adhesion-related signaling pathways, facilitating cell spreading and migration. Extracellular signal–regulated kinase (ERK) 1 and 2, implicated in tumor growth and survival, has also been linked to clinical melanoma progression. We have cloned the MCSP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
156
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(161 citation statements)
references
References 53 publications
3
156
0
2
Order By: Relevance
“…In addition, NG2 and α3β1 integrin are co-expressed and form a physical complex on the cell surface. Upon stimulation by phorbol-12-myristate-13-acetate (PMA) or PDGF, the motility of NG2-positive cells increases significantly compared to that of NG2-null cells [67,68] . Further investigation has shown that both PMA and PDGF trigger protein kinase C α (PKCα)-dependent phosphorylation of NG2 proteoglycan at Thr2256, and that this phosphorylation event is required for the increase of motility.…”
Section: Critical Roles Of Ng2 Cells and Ng2 Proteoglycan In Gliomamentioning
confidence: 99%
“…In addition, NG2 and α3β1 integrin are co-expressed and form a physical complex on the cell surface. Upon stimulation by phorbol-12-myristate-13-acetate (PMA) or PDGF, the motility of NG2-positive cells increases significantly compared to that of NG2-null cells [67,68] . Further investigation has shown that both PMA and PDGF trigger protein kinase C α (PKCα)-dependent phosphorylation of NG2 proteoglycan at Thr2256, and that this phosphorylation event is required for the increase of motility.…”
Section: Critical Roles Of Ng2 Cells and Ng2 Proteoglycan In Gliomamentioning
confidence: 99%
“…These include the activation of small Rho family GTPase Cdc42 and of the adaptor protein p130cas (Eisenmann et al, 1999), as well as the association of HMW-MAA with membrane-type 3 matrix metalloproteinase on melanoma cells (Iida et al, 2001). Furthermore, elevated HMW-MAA expression in early tumors has been proposed to facilitate tumor progression by enhancing the activation of focal adhesion kinase (FAK) and extracellular signal-regulated protein kinases 1 and 2 (ERK1/2) (Yang et al, 2004). The clinical relevance of these findings is indicated by the higher frequency of HMW-MAA expression in metastatic than in primary lesions in acral lentiginous melanoma (ALM), and by the association of HMW-MAA expression in primary ALM lesions with poor prognosis (Kageshita et al, 1991(Kageshita et al, , 1993.…”
Section: Introductionmentioning
confidence: 99%
“…17 NG2 also regulates FAK and ERK activation by distinct mechanisms in human melanoma cells. 13 However, regulation of FAK phosphorylation through proteoglycans in apoptosis has not been studied, and the role of NG2 in regulating apoptosis by the ECM is unknown.…”
mentioning
confidence: 99%
“…The chondroitin sulfate proteoglycan (CSPG) nerve/glial antigen 2 (NG2) and the a4b1 integrin have been proposed as coreceptors with distinct signaling roles in mediating the spread of melanoma cells on FN-coated surfaces. 12,13 Thus, NG2 might work in concert with a4b1 to regulate anoikis induced by an altered FN matrix.…”
mentioning
confidence: 99%